Local heat generation and material flow in friction stir welding of mild steel assemblies. (April 2016) - Micallef, Daniel; Camilleri, Duncan; Toumpis, Athanasios; Galloway, Alexander; Arbaoui, Larbi
In friction stir welding, assemblies are joined by means of plasticising, shearing and stirring non-molten material. The heat generation is directly related to the viscous behaviour of plasticised material, through coupled Navier–Stokes thermo-fluid flow stress equations. A significant amount of research has been conducted on aluminium friction stir welding but studies on mild steel assemblies are limited. The aim of this work is to understand the influence of the tool rotational and traverse speed on the resulting material stir zone shape and the heat power generated in friction stir welding of mild steel assemblies. A numerical and experimental approach is adopted in this study. Material visco-plastic properties are primarily established experimentally and are then applied to a computational fluid dynamics model through user-defined material flow stress constitutive laws. The model was further validated through a series of thermocouple and macrograph measurements and later on used to fulfil the aims of this work. This study identifies that the total heat generated for different welding parameters follows a non-linear variation with radial and angular tool position. These results provide a platform for the accurate definition of heat flux inputs and thermal strains to global thermo-elasto-plastic models, replacing more simplified linear specifications currently used in the literature.